2015
DOI: 10.11604/pamj.2015.22.41.7810
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel involvement documented by capsule endoscopy in Churg-Strauss syndrome

Abstract: Churg-Strauss syndrome is a small and medium vessel vasculitis and is also known as allergic granulomatous angiitis. Gastrointestinal involvement is common in patients with Churg-Strauss syndrome (20-50%). The most common symptoms are abdominal pain, diarrhoea and occasionally gastrointestinal bleeding and perforation. We present a case of Churg-Strauss syndrome with small bowel lesions documented by video capsule endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In such previous studies, ulcers or erythematous and nodular mucosa in the stomach, and/or ulcers or multiple small polyps in the duodenum were identified 15 24 . In some case reports, CE or BAE revealed that erosions, submucosal edema with lymphangiectasias and erythema, or ulcers of various shapes, such as multiple punched-out, small or irregular ulcers, were seen in the jejunum and ileum 25 26 27 28 . Colonoscopy showed mucosal erythema, erosion, ulceration, dark red sign or various red flares 10 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In such previous studies, ulcers or erythematous and nodular mucosa in the stomach, and/or ulcers or multiple small polyps in the duodenum were identified 15 24 . In some case reports, CE or BAE revealed that erosions, submucosal edema with lymphangiectasias and erythema, or ulcers of various shapes, such as multiple punched-out, small or irregular ulcers, were seen in the jejunum and ileum 25 26 27 28 . Colonoscopy showed mucosal erythema, erosion, ulceration, dark red sign or various red flares 10 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the entire length of the small intestine can be difficult. Recently, the use of double balloon endoscopy 19 and capsule endoscopy 20 have been reported in patients with EGPA. These techniques allow the identification of multiple ulcers in the small intestine that could lead to perforation.…”
Section: Discussionmentioning
confidence: 99%